Hearing Assessment of Neonates at Risk for Hearing Loss at a Hearing Health High Complexity Service: An Electrophysiological Assessment - Reis, Flavia Mara Fernandes da Silva; Gonçalves, Claudia Giglio de Oliveira; Conto, Juliana De; Iantas, Milena; Lüders, Débora; Marques, Jair (International Archives of Otorhinolaryngology, 2019)
Introduction Hearing is the main sensory access in the first years of life. Therefore, early detection and intervention of hearing impairment must begin before the first year of age.Objective To analyze the results of the electrophysiological hearing assessment of children at risk for hearing loss as part of the newborn hearing screening (NHS).Methods This is a cross-sectional study held at a hearing health public service clinic located in Brazil, with 104 babies at risks factors for hearing loss referred by public hospitals. A questionnaire was applied to parents, and the auditory brainstem response (ABR) test was held, identifying those with alterations in the results. The outcome of the NHS was also analyzed regarding risk factor, gestational age and gender.Results Among the 104 subjects, most of them were male (53.85%), and the main risk factor found was the admission to the neonatal intensive care unit (NICU) for a period longer than 5 days (50.93%). Eighty-five (81.73%) subjects were screened by NHS at the maternity and 40% of them failed the test. Through the ABR test, 6 (5.77%) infants evidenced sensorineural hearing loss, 4 of them being diagnosed at 4 months, and 2 at 6 months of age; all of them failed the NHS and had family history and admission at NICU for over 5 days as the most prevalent hearing risks; in addition, family members of all children perceived their hearing impairment.Conclusion Advances could be observed regarding the age of the diagnosis after the implementation of the NHS held at the analyzed public service clinic.
Keywords: hearing; risk factors; newborn screening; early diagnosis; hearing loss